2018
DOI: 10.1007/s11856-018-1691-3
|View full text |Cite
|
Sign up to set email alerts
|

Model-theoretic aspects of the Gurarij operator system

Abstract: We establish some of the basic model theoretic facts about the Gurarij operator system GS recently constructed by the second-named author. In particular, we show: (1) GS is the unique separable 1-exact existentially closed operator system;(2) GS is the unique separable nuclear model of its theory; (3) every embedding of GS into its ultrapower is elementary; (4) GS is the prime model of its theory; and (5) GS does not have quantifier-elimination, whence the theory of operator systems does not have a model compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…It is also proved in [28] that NP is the unique nontrivial metrizable noncommutative Choquet simplex with dense matrix extreme boundary, and A(NP) is the unique separable nuclear operator systems that is universal in the sense of Kirchberg and Wassermann [63]. The model-theoretic properties of the noncommutative Poulsen system have been investigated in [49]. The following noncommutative analog of Theorem 1.3 follows from our general results; see Subsection 8.2.…”
Section: Introductionmentioning
confidence: 60%
“…It is also proved in [28] that NP is the unique nontrivial metrizable noncommutative Choquet simplex with dense matrix extreme boundary, and A(NP) is the unique separable nuclear operator systems that is universal in the sense of Kirchberg and Wassermann [63]. The model-theoretic properties of the noncommutative Poulsen system have been investigated in [49]. The following noncommutative analog of Theorem 1.3 follows from our general results; see Subsection 8.2.…”
Section: Introductionmentioning
confidence: 60%
“…, P (q) q ) of the corresponding limit A(P (q) ) is the q-minimal Poulsen simplex. The model-theoretic properties of A(P), A(NP), and A(P (q) ) have been studied in [25].…”
Section: 1mentioning
confidence: 99%
“…Set K C * |L os := {A|L os : A ∈ K C * }. In [6], the following question was raised: is K C * |L os an elementary class? The main result of this note is to give an affirmative answer to this question.…”
mentioning
confidence: 99%
“…If K C * |L os were ∀∃-axiomatizable, then there would be A ∈ K C * |L os that is existentially closed for K C * |L os . However, in [6,Section 5], it was observed that if φ : X → Y is a complete order embedding that is also existential, then φ maps unitaries to unitaries. Take a complete order embedding of A into a C * -algebra B that is not a * -homomorphism (see, for example, [6, Section 5]); since this embedding maps unitaries to unitaries (since A is existentially closed for K), this contradicts Corollary 15.…”
mentioning
confidence: 99%
See 1 more Smart Citation